Регіонально-економічні проблеми розвитку сільського господарства і промислу Північно-західної України в дослідженнях доктора Мирона Кордуби - Ємчук, Тетяна Володимирівна; Руденко, Валерій Петрович; Грек, Катерина (Вісник Чернівецького торговельно-економічного інституту, 2021)
Relevance and problem statement. Professor Myron Korduba (1876 – 1947), an outstanding Ukrainian scientist, is among the most essential contributors to the development of historic, economic, geographical and toponymic sciences. In said areas, he prepared and published over 450 scientific works, and a great portion of these is found as author’s handwriting still little known to contemporaries. “Pivnichno-Zakhidna Ukraina” (North-Western Ukraine), Myron Korduba’s monograph, was among the author’s most fundamental studies which saw the light in Vienna in 1917. The work’s focus – over one third of the monograph – is the exposure of regional-economic problems of development of agriculture and economy within these lands that covered the part of Horodnenska Province, south-western part of Minsk Province, historical Volyn’ and Holmshchyna. The present work aims at highlighting major regional-economic problems of development of agriculture and economy in North-Western Ukraine in the eyes of Myron Korduba on the eve of World War I and still little known to present-day scientists. Study results. Doctor Myron Korduba presented a deep and comprehensive analysis of regional-economic problems of development of agriculture and economy in North-Western Ukraine. Territorial differentiation in the structure of land use was disclosed. Regional differences in land distribution between their owners were established. Land value within a group of private owners was estimated. Productivity of plant growing – a principal branch of farming in the region – was thoroughly analyzed as well as perspectives of its development were given an outline. A distressing conclusion was made with respect to significant backwardness of cattle breeding in North-Western Ukraine on a general European level. Economic developmental problems of the region were pronounced aloud. Among these – poorness in mineral resources; expressed inequality in industrial development between regional provinces and districts; with regard to sectoral structure – processing of plant and cattle food, woodcrafts and forest economy comprised 4/5 of overall production. Prevalence of small firms in the structure of regional economy, low costs of annual per capita production were the most essential specificities of regional development. Practical value. Materials of the article can be used for lecturing general and special courses in economic history and regional economics. Perspectives of further studies. Overall assessment of Professor Myron Korduba’s creative heritage.
Regional-economic problems of development of agriculture and economy of North-Western Ukraine in Doctor Myron Korduba’s studies
Економічної географії та екологічного менеджменту
Keywords: Мирон Кордуба; регіонально-економічні проблеми; сільське господарство; промисел; Північно-західна Україна